Braille Media in Vocabulary Learning for Blind Students at Special Needs School: A Review of Educational Psychology - Ariswanto, Ariswanto; Muktamar, Ahmad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Blind children in special needs schools struggle to learn the Arabic language without visual aid. Educational psychology must study how to maximize the learning medium for blind students' psychological and tactile demands. This study aims to explore and describe the effectiveness of using Braille media in teaching Arabic vocabulary to blind students, especially from an educational psychology perspective that includes cognitive aspects, motivation, and the language acquisition process. This study uses a descriptive qualitative approach. The subjects of the study were blind students at SLB-A YAPTI Makassar. Data collection was carried out through participant observation, in-depth interviews with teachers and students, and analysis of learning documents to gain a comprehensive understanding of the implementation and impact of Braille in the vocabulary learning process. The results of the study indicate that Braille media has high effectiveness as the main tool in learning Arabic vocabulary for blind students. From an educational psychology perspective, Braille functions as a cognitive facilitator that allows students to activate tactile-kinesthetic memory, improve concentration, and build linguistic schemes in a structured manner. The use of Braille, integrated with appropriate teaching methods, has also been shown to increase students' intrinsic motivation due to their independence in accessing and processing vocabulary materials. Vocabulary retention is also more optimal due to multi-sensory engagement. This study adds to educational psychology and special education literature by examining how Braille media helps visually impaired students learn foreign languages. It helps teachers and curriculum developers create successful and inclusive language teaching tools that accommodate visually impaired kids' specific psychological mechanisms.